2008
DOI: 10.1111/j.1365-2672.2007.03612.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacteriocin production and virulence traits in vancomycin-resistant enterococci of different sources

Abstract: Aim:  Three hundred and two enterococci were isolated from food, animal and clinical samples in order to evaluate the incidence of vancomycin‐resistant enterococci (VRE) and bacteriocin, cytolysin, haemolysin, gelatinase production. Methods and Results:  Among the isolates, 27 (8·9%) were VRE, and 17 (63%) of these showed, by the deferred antagonism method, bacteriocin production against Gram‐positive and some Gram‐negative indicators. Eight bacteriocin producers displayed by polymerase chain reaction an enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
30
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 61 publications
7
30
0
1
Order By: Relevance
“…However, recent investigation described different incidences in clinical isolates; for instance, Sabia et al reported that 70% of vancomycin resistance enterococci isolates carried the gelE; they also found gelatinase activity in E. faecalis species more than E. faecium. Nevertheless, Sharifi et al detected gelE with 7.9% of vancomycin resistance enterococci in Hospitalized Patients of Northwest of Iran (17,22). Previous studies have indicated the importance and frequency of gelatinase enzyme in enterococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent investigation described different incidences in clinical isolates; for instance, Sabia et al reported that 70% of vancomycin resistance enterococci isolates carried the gelE; they also found gelatinase activity in E. faecalis species more than E. faecium. Nevertheless, Sharifi et al detected gelE with 7.9% of vancomycin resistance enterococci in Hospitalized Patients of Northwest of Iran (17,22). Previous studies have indicated the importance and frequency of gelatinase enzyme in enterococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although a screening for production of bacteriocins by E. faecalis and E. faecium was the subject of several previous studies [10][11][12][13][14], only little information is available about this feature in E. avium, E. hirae, E. mundtii, E. casseliflavus and E. durans isolated from different environments. The aim of this study was to screen the production of antimicrobial activities as well as the presence of bacteriocin structural genes in enterococcal isolates include diverse species isolated from different sources in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, las especies vinculadas a patologías humanas quedan limitadas a E. faecalis y E. faecium mientras que las restantes resultan agentes etiológicos infrecuentes (Sabia et al, 2008).…”
Section: Introductionunclassified